Risk Management – Decision Making Using Analytical Hierarchy Process - P Asrani, Neha; Venkatasubramanian, C; Muthu, D; S, Padmashree; Ramakrishnan, K (International Journal of Engineering and Technology, 2018)
A risk assessment practice determines the risk both quantitatively and qualitatively, such that risks are analysed and assessed thoroughly. Several methods are available to mitigate the failures in a construction project. This project focuses on identifying risks and mitigating them to reduce failures. On a questionnaire basis, a survey from various employees working on different projects is conducted by considering seven major factors of risks and the normalised score of each factor is ranked. Based on the normalized score values, least three risk factors were identified and Analytical Hierarchy Process(AHP) is applied by manual calculations. AHP is based on human judgements and objective evaluation, which examines the consistency of the evaluation by Eigen values. Validation of the identified factors is also done through MAT Lab and is compared with the manual method. Consistency and hierarchy of the identified factors has been found out, thereby mitigating the failures and increasing the efficiency of the projects.Â Â